New perspectives on Hispanic contact : linguistics in the Americas - Sessarego, Sandro; González-Rivera, Melvin (Lengua y sociedad en el mundo hispánico, 2015)
"...Characterizes the nature of the contact situation: Spanish in contact with indigenous languages; Spanish in contact with coerced-migration languages; Spanish in contact with free-migration languages; and Spanish in contact with languages outside of Latin America but still within the Americas"-- Page [4] of cover.